Pengembangan Model Pohon Keputusan untuk Menentukan Jurusan Pada SMA Menggunakan Bahasa C++ - Mustofa, Rangga Ali; Azzahra, Salsabila Nida; Priswati, Hasna Putri; Martadisastra, Muhamad Rafi Pasya; Munawir, Munawir; Perdana, Abdi Surya (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The selection of a high school major is one of the crucial decisions that will determine the future of students. Decision Support Systems (DSS) can be used to assist students in making such decisions. DSS can provide information and advice to students based on relevant criteria. The decision tree method is one of the classification methods that can be applied to DSS. This method utilizes a tree representation consisting of several nodes. Nodes in the decision tree represent attributes that influence decision-making in specific cases. This research aims to develop a decision tree model using the C++ programming language to assist high school students in choosing their majors. The decision tree model is developed by considering relevant criteria, namely interests, talents, and grades obtained by students in various subjects. The research results indicate that the developed decision tree model can provide relevant information and advice to students in choosing their majors. This model can significantly contribute to the effectiveness of the decision-making process undertaken by high school students when selecting their majors.